Previous short-term use of testosterone propionate enhances muscle hypertrophy in Wistar rats submitted to ladder-based resistance training - Lourenço, Ítalo; Krause Neto, Walter; Amorim, Laura dos Santos Portella; Ortiz, Vagner Moraes Munhoz; Geraldo, Vitor Lopes; Ferreira, Gabriel Henrique da Silva; de Lima, Jackson Torres; Massoni, Amanda Alves Ribeiro; Oliveira, Beatriz Massensini; Anaruma, Carlos Alberto [UNESP]; Ciena, Adriano Polican [UNESP]; Gama, Eliane Florencio; et al. (Elsevier, 2022)
To investigate the effects of the previous administration of testosterone propionate (TP) on the morphology of the gastrocnemius muscle of Wistar rats submitted to ladder-based resistance training (LRT). Twenty-eight rats were divided equally into groups: initial control (CI), 4-week TP (CT4), 4-week TP + LRT (TRT), and placebo + LRT (RT). The rats from the CT4 and TRT groups were treated with TP for four weeks (10 mg/kg/week). TRT and RT trained for ten weeks. The rodents were euthanized at the end of the experiment, and gastrocnemius muscle, prostate, and left and right testicles were collected. There was no statistical difference between the RT and TRT for final volume load. The prostate mass of the TRT and RT groups was statistically heavier than the CT4 group (P < 0.01). The TRT group's prostate/body mass ratio was statistically different from the CT4 group (P < 0.05). The TRT group was shown to have larger type I, type II, and mean fCSA fibers than all other groups (P < 0.001). Regarding the nuclei/fiber ratio (N/f), the CT4, RT, and TRT groups had higher values than CI (P < 0.01). In addition, the RT group showed a higher N/f ratio than CT4 (P < 0.001) but lower than TRT (P < 0.001). In conclusion, short-term TP administration before resistance training can elicit a greater N/f ratio and size of the mean fCSA of the Gastrocnemius muscle of young adult Wistar rats than resistance training alone.
Keywords: Exercise; Morphology; Skeletal muscle; Steroids; Testosterone